Modelling intestinal glucose absorption in premature infants using continuous glucose monitoring data. (April 2019) - Knopp, J.L.; Signal, M.; Harris, D.L.; Marics, G; Weston, P.; Harding, J.; Tóth-Heyn, P.; Hómlok, J.; Benyó, B.; Chase, J.G.
Highlights: A two compartment model of glucose transfer and absorption in the digestive system is proposed for modelling milk feeds in infants. Continuous glucose monitor (CGM) data is used to examine the appearance of glucose peaks in the blood associated with oral/enteral feed intake. The half life of absorption of glucose from the gut to the blood stream was found to be approximately 50 min. This is a non-invasive method of estimating gut absorption of glucose in a premature infant cohort, which enables improved modelling of glucose appearance for glycaemic control. Abstract: Background: Model-based glycaemic control protocols have shown promise in neonatal intensive care units (NICUs) for reducing both hyperglycaemia and insulin-therapy driven hypoglycaemia. However, current models for the appearance of glucose from enteral feeding are based on values from adult intensive care cohorts. This study aims to determine enteral glucose appearance model parameters more reflective of premature infant physiology. Methods: Peaks in CGM data associated with enteral milk feeds in preterm and term infants are used to fit a two compartment gut model. The first compartment describes glucose in the stomach, and the half life of gastric emptying is estimated as 20 min from literature. The second compartment describes glucose in the small intestine, and absorption of glucose into the blood is fit to CGM data. Two infant cohorts from two NICUs are used, and results are compared to appearances derived from data in highly controlled studies in literature. Results: The average half life across all infants for glucose absorption from the gut to the blood was 50 min. This result was slightly slower than, but of similar magnitude to, results derived from literature. No trends were found with gestational or postnatal age. Breast milk fed infants were found to have a higher absorption constant than formula fed infants, a result which may reflect known differences in gastric emptying for different feed types. Conclusions: This paper presents a methodology for estimation of glucose appearance due to enteral feeding, and model parameters suitable for a NICU model-based glycaemic control context.